Indonesian Sub-Majors at Chinese Universities and Belt and Road Initiative (BRI) - Isyana Adriani (President University, 2018)
Since President of China Xi Jinping introduced the mega infrastructure project Belt and Road Initiative (BRI) in late 2013, many have doubted the real objective of the president, particularly since world leadership position has been vacant because US President Donald Trump still has no clear foreign policy on Asia Pacific. BRI, which aims to connect China to all continents in the world, has already had negative and positive impacts. One of which is Africa, where China has been helping the Trans-African Highway project, a project that has been planned since 1971. However, BRI has caused African countries’ debts to China to multiply, and it is not impossible that they will experience what Sri Lanka has already experienced: Beijing taking over their Hambantota Port. In Indonesia itself, there have been several BRI projects, such as the 142-km fast train that connects Bandung, West Java, to Jakarta, and Morowali Industrial Park in Central Sulawesi. However, despite BRI’s help with infrastructure many people are suspicious that Indonesia will fall into a “debt trap” like Sri Lanka and African countries already did. They are also worried about the ever-increasing number of Chinese workers to Indonesia, which threaten the availability of jobs for locals. On the other hand, Indonesia’s involvement in BRI shows that Indonesia is an important country to China, and this can be seen through many things, one of which is the growing number of Chinese universities having Indonesian language and culture sub-majors in the past seven years. This essay focuses on how these Indonesian language and culture sub-majors contribute to the success of BRI in China.